2019
DOI: 10.1002/jocb.409
|View full text |Cite
|
Sign up to set email alerts
|

Insight Out: Making Creativity Visible

Abstract: Models of creative problem solving are predicated upon mental states to explain everything from the outcome of problem-solving experiments to the emergence of artistic creativity. We present two converging perspectives that describe a profoundly different ontological description of creativity. Our analysis proceeds from a distinction between first-order problem solving, where the agent interacts with a physical model of the problem and second-order problem solving, where the agent must cogitate a solution to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 46 publications
(50 reference statements)
0
29
0
Order By: Relevance
“…Without postulating the notion of “object agency” as some anthropologists or archeologists would (Feldman, 2010), we must consider how creative agency is actively distributed between person and environment through the means of action and interaction. The well-established metaphor of the dialogue between artist and his or her tools needs to be theorized further and there have been, in recent years, decisive steps taken toward developing a much more material account of creative action (see, for example, the notion of outsight in Vallée-Tourangeau & March, 2019). For the sociocultural theory of creativity outlined here, it is central to recognize that creative action does not follow a linear path that starts from the creator’s vision (or perspective), makes use of those affordances that align with the vision, and ends in a product that reflects the initial vision, more or less; on the contrary, a better description of it would be the back and forth movement between creator and object, intentions and accidents, perspectives that reveal new affordances and discovered affordances that guide new perspectives.…”
Section: A Perspective-affordance Theory Of Creativitymentioning
confidence: 99%
“…Without postulating the notion of “object agency” as some anthropologists or archeologists would (Feldman, 2010), we must consider how creative agency is actively distributed between person and environment through the means of action and interaction. The well-established metaphor of the dialogue between artist and his or her tools needs to be theorized further and there have been, in recent years, decisive steps taken toward developing a much more material account of creative action (see, for example, the notion of outsight in Vallée-Tourangeau & March, 2019). For the sociocultural theory of creativity outlined here, it is central to recognize that creative action does not follow a linear path that starts from the creator’s vision (or perspective), makes use of those affordances that align with the vision, and ends in a product that reflects the initial vision, more or less; on the contrary, a better description of it would be the back and forth movement between creator and object, intentions and accidents, perspectives that reveal new affordances and discovered affordances that guide new perspectives.…”
Section: A Perspective-affordance Theory Of Creativitymentioning
confidence: 99%
“…It has been widely asserted and empirically demonstrated that the socio-materiality of environments plays a central role in creative sensemaking and creative production (Glăveanu, 2020;Tanggaard, 2013;Tanggaard & Beghetto, 2015;Vallée-Tourangeau & March, 2019). In the context of painting for instance, the paints, the brushes and the canvas shape the final painting as much as the artist's 1…”
Section: Role Of Technology In Creativitymentioning
confidence: 99%
“…In a recent critique of insight as an explanatory model of problem solving, Vallée-Tourangeau and March (2019) introduce the term ‘outsight’ to describe how problem solving may take place by observing and manipulating the environment. Outsight provides a more parsimonious explanation for the emergence of Jōmon pottery.…”
Section: Met and Typologymentioning
confidence: 99%